2005
DOI: 10.1016/j.surfcoat.2004.04.083
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline-coated iron: studies on the dissolution and electrochemical activity as a function of pH

Abstract: Polyaniline coatings were electrodeposited from an oxalic acid solution onto iron and their electrochemical activity and corrosion protection properties studied as a function of pH. It was found that the coating (emeraldine salt) had a limited effect on the corrosion protection of iron in acidic solutions. However, in an alkaline borate solution, where the conducting polyaniline was converted to the emeraldine base, the coating had a clear beneficial effect on the local breakdown of iron by chloride anions; mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…We can observe that the electrical conductivity of POA nanoparticles pure is in the range of insulator [10][11][12][13][14][15][16] ; as shown in figure (3); but when added different metal oxides nanopowder; it was found that the electrical conductivity of poly anisidine nanoparticles was improved.…”
Section: Conductivity Measurementsmentioning
confidence: 91%
See 1 more Smart Citation
“…We can observe that the electrical conductivity of POA nanoparticles pure is in the range of insulator [10][11][12][13][14][15][16] ; as shown in figure (3); but when added different metal oxides nanopowder; it was found that the electrical conductivity of poly anisidine nanoparticles was improved.…”
Section: Conductivity Measurementsmentioning
confidence: 91%
“…Polyaniline and its derivatives are mainly used as coating to improve the corrosion resistance of oxidizable metals. These coatings have also been considered for several applications such as the electronic industry; biosensor applications [10][11][12][13][14][15][16]. Polyaniline has shown variety of applications such as in rechargeable batteries; electro catalysis; electrochromic displays; gas separation; and biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…equivalent electrical circuit model and the Nyquist complex plane plots recorded in aqueous 3.5% NaCl. In equivalent electrical circuit, Rs represents the electrolyte resistance, CPE c is the constant phase element referred as coating capacitance which is connected parallel with the coating pore resistance, R po , the constant phase element that represents all the frequency dependent electrochemical phenomena, namely double layer capacitance, CPE dl and diffusion processes, and R ct the charge transfer resistance connected with corrosion processes in the bottom of the pores, 2,[24][25][26] The constant phase element, CPE, is introduced in the circuit instead of a pure capacitor to give a more accurate fit and compensate nonhomogeneity of coating. 27,28 The Nyquist complex plane plot of bare Cu can be fitted with model shown in Figure 5, with one semicircle.…”
Section: Electrochemical Impedance Spectroscopy (Eis) Studiesmentioning
confidence: 99%
“…7,9,14,48 The second semicircle in the low frequency region is attributed to the polymer/ LCS interface and it is characterized by R ct for the charge transfer reactions occurring at the bottom of the pores in the coating and CPE p . 7,9,14,48 The values of the impedance parameters of the best fit to the experimental impedance plots for uncoated LCS and polymer coated LCS are given in Table II about $ 19, 7, 16, and 36 times higher than that observed for uncoated LCS. The protective effect of PANI, POA, POA/PANI, and PANI/POA is obvious as the R ct values are significantly higher as compared to the uncoated LCS.…”
Section: Eis Studiesmentioning
confidence: 99%